Global Economic Prospects, June 2022 - World Bank (Washington, DC: World Bank, 2022)
The world economy continues to suffer from a series of destabilizing shocks. After more than two years of pandemic, the Russian Federation’s invasion of Ukraine and its global effects on commodity markets, supply chains, inflation, and financial conditions have steepened the slowdown in global growth. In particular, the war in Ukraine is leading to soaring prices and volatility in energy markets, with improvements in activity in energy exporters more than offset by headwinds to activity in most other economies. The invasion of Ukraine has also led to a significant increase in agricultural commodity prices, which is exacerbating food insecurity and extreme poverty in many emerging market and developing economies. Numerous risks could further derail what is now a precarious recovery. Among them is, in particular, the possibility of stubbornly high global inflation accompanied by tepid growth, reminiscent of the stagflation of the 1970s. This could eventually result in a sharp tightening of monetary policy in advanced economies to rein in inflation, lead to surging borrowing costs, and possibly culminate in financial stress in some emerging market and developing economies. A forceful and wide-ranging policy response is required by policy makers in these economies and the global community to boost growth, bolster macroeconomic frameworks, reduce financial vulnerabilities, provide support to vulnerable population groups, and attenuate the long-term impacts of the global shocks of recent years.